Preparation of a silicon micro-strip nuclear radiation detector by a two-step annealing process - 李海霞 李占奎 王方聪 王柱生 王秀华 李春艳 (Chinese physics C, 2011)
The annealing process for boron implantation is a crucial step during large size nuclear radiation detector fabrication. It can reduce the lattice defects and the projection straggling. A two-step annealing process for boron implantation was developed instead of a one-step annealing process, and the reverse body resistance of a silicon micro-strip detector was significantly increased, which means that the performance of the detector was improved.